1 Pictorial evolution of focal myocardial fibrosis in duchenne muscular dystrophy (DMD). (October 2018) - Connolly, M; Fallon, A; O'Hanlon, R; Waterhouse, D
Abstract : Introduction: Interstitial myocardial fibrosis is best detected and quantified by cardiovascular magnetic resonance (CMR). It may be accurately detected by late gadolinium enhancement (LGE) and T1 relaxation mapping. Duchenne muscular dystrophy (DMD) is an X-linked recessive disease that occurs in males leading to cardiomyopathy and death in early adulthood. This report describes the use of CMR to detect early cardiac manifestations in DMD and to evaluate its progression over a five-year period in two young patients. Methods: Yearly CMR was performed on two brothers (patient one aged 16 and patient two aged 14) from 2013 until 2017. All patients underwent LGE imaging for myocardial scar using a segmented Inversion recovery-technique 10 to 15 min after injection of 0.1 mmol/kg of gadolinium. Myocardial enhancement was assessed visually and interpreted by two cardiac CMR-trained physicians. T1 mapping techniques were used on the latest scan in November 2017. Results: A short axis stack of LGE imaging from patient one is shown in figure 1 which demonstrates significant, confluent myocardial fibrosis in the anterolateral, lateral and inferolateral walls from base through to the distal LV segments. The total gadolinium volume was 15 g (24% of the total myocardium), with a T1 mapping value of 1105 ms (normal local mean 957 ms), figure 2. Figure 3 highlights the evolution of DMD in these two patients from 2013–2017 which shows a gradual increase in LGE throughout the horizontal long axis (HLA) and short axis (SA) images of each patient. There has been a clear deterioration in appearances with the most striking images of LGE seen in November 2017. Conclusion: LGE is a sensitive parameter for the early diagnosis of cardiomyopathy in DMD and can be used to show progression of disease.